Survival After Neoadjuvant and Adjuvant Treatments Compared to Surgery Alone for Resectable Esophageal Carcinoma: A Network Meta-analysis. Issue 3 (March 2017) - Pasquali, Sandro; Yim, Guang; Vohra, Ravinder S.; Mocellin, Simone; Nyanhongo, Donald; Marriott, Paul; Geh, Ju Ian; Griffiths, Ewen A.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: This network meta-analysis compared overall survival after neoadjuvant or adjuvant chemotherapy (CT), radiotherapy (RT), or combinations of both (chemoradiotherapy, CRT) or surgery alone to identify the most effective approach. Summary Background Data: The optimal treatment for resectable esophageal cancer is unknown. Methods: A search for randomized controlled trials reporting on neoadjuvant and adjuvant therapies was conducted. Using a network meta-analysis, treatments were ranked based on their effectiveness for improving survival. Results: In 33 eligible randomized controlled trials, 6072 patients were randomized to receive either surgery alone (N = 2459) or neoadjuvant CT (N = 1332), RT (N = 58), and CRT (N = 1196) followed by surgery or surgery followed by adjuvant CT (N = 542), RT (N = 383), and CRT (N = 102). Twenty-one comparisons were generated. Neoadjuvant CRT followed by surgery compared with surgery alone was the only treatment to significantly improve survival [hazard ratio (HR) = 0.77, 95% confidence interval (CI): 0.68–0.87]. When trials were grouped considering neoadjuvant and adjuvant therapies and surgery alone, neoadjuvant therapies combined with surgery compared with surgery alone showed a survival advantage (HR = 0.83, 95% CI 0.76–0.90), whereas surgery along with adjuvant therapies showed no significant survival advantage (HR = 0.87, 95% CI 0.67–1.14). A subgroup analysis of neoadjuvant therapies showed a superior effectiveness of neoadjuvant CRT and surgery compared with surgery alone (HR = 0.77, 95% CI 0.68–0.87). Conclusions: This network meta-analysis showed neoadjuvant CRT followed by surgery to be the most effective strategy in improving survival of resectable esophageal cancer. Resources should be focused on developing the most effective neoadjuvant CRT regimens for both adenocarcinomas and squamous cell carcinomas of the esophagus.